Utilizing molecular docking and cell validation to explore the potential mechanisms of lupenone attenuating the inflammatory response via NF-κB pathway - Wang, Xiangpei (2024)
Diabetic nephropathy (DN), a common microvascular complicating disease of diabetes. Lupenone, a pentacyclic triterpenoid, has anti-inflammatory effects and can prevent type 2 diabetes mellitus and treat renal damage, however, the effects and mechanisms of lupenone in DN remain unclear. Thereby,the MTT method was used to investigate the antiproliferative effect of lupenoneon the cell line rat glomerular mesangial cells (HBZY-1). Molecular docking was used to investigate the combination of lupenone and MCP-1, IL-1β, TNF-α, IKKβ, IκBα, and NF-κB p65 proteins. The expression of mRNA of the pro-inflammatory cytokines (MCP-1, IL-1β and TNF-α) and the NF-κB signalling pathway in HBZY-1 cells were assessed by RT-PCR. The protein expressions of pro-inflammatory cytokines and NF-κB pathway were got by Western blot. Result showed that lupenone inhibited the proliferative activity of HBZY-1 cells at non-cytotoxic concentrations. Molecular docking results showed that lupenone combined well with the target proteins. Moreover, lupenone could significantly reduced the mRNA and protein expressions for pro-inflammatory cytokines and IKKβ, p-p65 and p-IκBα. Lupenone may play an anti-inflammatory role in DN treatment by inhibiting the NF-κB signalling pathway. These results provided a new understanding of the pharmacological mechanisms of lupenone in treatment of DN.